Korean Moon: Waxing or Waning? - Sandon, Leo (Theology today, 1978)
“Unification theology is eclectic, syncretistic, and esoteric. … In whatever phase of its life the Moonist movement is now, it raises crucial questions for those of us who are confessing Christians. Perhaps the Moonies are sending us a message about the nature of conversion and commitment among young adults; about the need for an adequate eschatological perspective; about the need for thoughtful morality and spirituality; and about the hunger in America for community.”